Effectiveness Of Oxytocin Massage On Breast Milk Production In Postpartum Mothers - Agnes Batmomolin; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2025)
Suboptimal breast milk production during the postpartum period is one of the causes of failure in exclusive breastfeeding. Psychological factors, fatigue, and lack of oxytocin stimulation can inhibit milk production. Oxytocin massage is a non-pharmacological intervention aimed at stimulating oxytocin to increase milk production and release. This study aimed to determine the effectiveness of oxytocin massage on breast milk production in postpartum mothers. This study uses a quasi -experimental design with a one-way approach. group Pretest - posttest. The sample consisted of 30 postpartum mothers selected using purposive sampling. Breast milk production was measured using indicators of smooth flow and frequency of breastfeeding. Data were analyzed using the Wilcoxon test Signed Rank Test. The results of the study showed an increase in breast milk production after oxytocin massage with a p value = 0.000 (<0.05). The conclusion of this study is that oxytocin massage is effective in increasing breast milk production in postpartum mothers.